Implications of the liquidity crisis in the Baltic-Nordic region - Ivo Karilaid; T\~onn Talpsepp; Tarvo Vaarmets (Baltic Journal of Economics, 2014)
This paper provides a more thorough empirical examination of the development and determinants of the liquidity position in the financial sector during the last financial crisis in the Baltic-Nordic region, which takes into consideration the whole economic cycle. The current study serves as an extension to an ex-ante study which was made in 2010. We look at fiscal and monetary policy implications of the liquidity problems arising in the crisis and stabilization process after that. The results show that the changes (and the speed of changes) of interest rates, GDP and money supply have occurred relatively fast, meaning that the rising area of the LM curve has been shorter than theory would predict. Market reactions took place quickly and simultaneously – there was no time for the slow restructuring, thus liquidity needs were higher than generally.
Keywords: G01; G21; 330; capital flows; financial crisis; liquidity position; policy implications